Pelatihan penggunaan Zoom Meeting untuk endidikan dan pelatihan di BKPSDM kabupaten Wakatobi - Amin Irmawan (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
The use of information technology in training has posed a challenge to the sustainability of traditional training methods, be it at a slow or rapid pace. In the post-Covid-19 era, often referred to as the "new normal," the training landscape has demanded a paradigm shift from conventional to technology-based training. The transformation of training through the adoption of technology applications and e-learning has emerged as a viable solution. This study examines the strategic issues faced by the Government of Wakatobi Regency concerning Education and Training, primarily limited personnel/officials in the Civil Service Agency and Human Resources Development Agency of Wakatobi Regency, with limited proficiency in information technology and inadequate infrastructure to meet information technology standards. The collaborative community engagement initiative with the Civil Service Agency and Human Resources Development Agency of Wakatobi Regency through Zoom Meeting-based training has yielded highly positive outcomes, contributing to the implementation of sustainable training programs and enhancing the institution's readiness to conduct online technical and functional training or Diklat. Furthermore, this engagement has significantly increased the capacities of personnel in the field of information technology for educational and training purposes. As part of a continuous effort, this community engagement activity has also supported the institution in planning and budgeting for the provision of appropriate infrastructure for online Education and Training, earmarked for the fiscal year 2024.